A fast, analytically based method to optimize local transmit efficiency for a transmit array. Issue 1 (14th February 2013) - Carluccio, Giuseppe; Collins, Christopher M.; Erricolo, Danilo
<x xml:space="preserve">Abstract</x> Purpose To develop an analytically based algorithm for rapid optimization of the local radiofrequency magnetic <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zsg8jmh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(B1+)</alternatives> field intensity for a given radiofrequency power through a transmit array. The analytical nature of the method will yield insight to optimization requirements and provides a valuable reference for numerically based searches. Methods With the knowledge of the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zsg8jn2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> field distribution generated by each single coil of the array, both the phases and the amplitudes of each coil current are optimized to maximize the magnitude of the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zsg8jjd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> field in a specific location of the body per unit of power transmitted through the array and, consequently, minimizing the whole body specific absorption rate for a given pulse sequence. Results Simulations considering the human body show that the proposed method can reduce the whole‐body specific absorption rate for a given <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zsg8jkz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> magnitude at the location of interest by a factor of about 6.3 compared to the classic birdcage current configuration, and by a factor of 3.2 compared to phase‐only shimming in a case with significant coupling between the elements of the array. Conclusion The proposed method can rapidly provide valuable information pertinent to the optimization of field distributions from transmit arrays. Magn Reson Med 71:432–439, 2014. © 2013 Wiley Periodicals, Inc.